Institutionally endorsed reputation for CSR leadership and the textual characteristics of CEO letters in CSR reports - Lourenço, I.; Oliveira, J.; Castelo, M.; Inácio, A. S. (Sustainability Accounting, Management and Policy Journal, 2025)
Purpose The purpose of this study is to examine the readability and length of CEO letters in the corporate social responsibility (CSR) reports of the US firms included in the North America DJSI Eligible Universe. Design/methodology/approach Data analysis is based on regression models. Findings Firms with a reputation for CSR leadership (those in the Dow Jones Sustainability Index [DJSI firms]) present larger CEO letters, but within these firms, those with lower financial performance stand out for presenting even lengthier narratives. Only firms with reputation for leadership in CSR enjoying high financial performance present more readable CEO letters when compared to firms lacking such reputation. Research limitations/implications This study contributes to the literature by proposing a multi-signal approach to the study of CSR reporting and emphasizing the importance of looking at institutional endorsements of CSR performance and financial performance interconnectedly. Practical implications This study can help managers and organizations become aware of the various forces that could drive the need for CSR communication and help them to be responsive to stakeholder audiences by communicating information about the organization’s socially responsible strategies and activities. Social implications This study’s theoretical argument and findings suggest the corporate stakeholders and policymakers should examine differently CSR reports from firms with and without institutionally endorsed CSR performance while also considering their levels of financial performance. Originality/value This study uniquely takes a multi-signal lens of analysis to examine the associations between textual characteristics of CSR narratives and CSR performance and financial performance.